PENERAPAN TEORI ADMINISTRASI PUBLIK DALAM KEBERLANJUTAN PENGELOLAAN IPAL KOMUNAL DI JAKARTA - Tanjung, Fadly Haley (LPPM Universitas Terbuka, 2022)
SANIMAS-IsDB Program was initiated by the Ministry of Public Works and Housing during 2015-2018 and Jakarta Capital City Government had contributed to build Communal WWTP in 23 locations. Bappenas (2018) showed that 96% of water body in Jakarta has been highly polluted and based on Environment Agency’s data in 2018, 72,7% contributions of that come from domestic wastewater. To make it operates well, a good and sustainable operation management required. According to PPAPP Agency, the best operating plant located in RW.01 Rawajati, Pancoran, Jakarta. Management operational indicators of Communal WWTP related to public administration theory. Gulick in Ahmad (2015) stated the aspects called POSDCORB (Planning, Organizing, Staffing, Directing, Coordinating, Reporting, Budgeting). These management aspects need to be elaborated with limitations in infrastructure management (Naipospos, 2019). Research Method that applied was qualitative descriptive, with preceded by literature study. The results were certain indicators that affects sustainable operational of the plant, and its relation with public administration theory, as follows: 1) The importance of stakeholders’ participation-related with aspect P, S, O and C; 2) Operation and maintenance costs-related to aspect O and B; 3) Technical design-related to aspect P; and 4) Social aspect-related to aspect R. Based on this, research consclusion is that stakeholders’ participation, technical design and social aspect are indicators related to P, S, O, C and R aspect, needs to be maintain to make a sustainable management. Otherwise, the operation and maintenance cost indicator related to aspect B, need to solve, increase, and become more priority in the management.